Pengaruh Pendidikan Terhadap Kinerja Pegawai Kantor Kecamatan Karangpenang Kabupaten Sampang dengan Profesionalisme sebagai Variabel Intervening - Chamariyah Chamariyah; Mei Indrawati; Mahsun Mahsun (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Mahsun, 2024. The Influence of Education on the Performance of Employees at the Karangpenang District Office, Sampang Regency with Professionalism as an Intervening Variable, Postgraduate Program, Wijaya Putra University. The type of research is explanatory, the research approach used is quantitative, the research sample is 56 respondents. Data analysis using SPSS and PLS analysis. The objectives of this study are: 1) To test and analyze the effect of education on the performance of employees at the Karangpenang District Office, Sampang Regency; 2) To test and analyze the effect of education on the professionalism of employees at the Karangpenang District Office, Sampang Regency; 3) To test and analyze the effect of professionalism on the performance of employees at the Karangpenang District Office, Sampang Regency; 4) To test and analyze the indirect effect of education on the performance of employees at the Karangpenang District Office, Sampang Regency mediated by professionalism. The results of the study indicate that: 1) Education has a significant effect on the performance of employees at the Karangpenang District Office, Sampang Regency with an original sample value of 0.142; 2) Education has a significant effect on the professionalism of the Karangpenang District Office, Sampang Regency with an original sample value of 0.314; 3) Professionalism has a significant effect on the performance of employees of the Karangpenang District Office, Sampang Regency with an original sample value of 0.464; 4) Employee education has a significant effect on the performance of employees of the Karangpenang District Office, Sampang Regency mediated by professionalism with an original sample value of 0.145.